Experimental Analysis on the Curing and Adhesive Behaviour of Standard Moisture-cured and Fast-cured Polyurethanes Used in Automotive Industry - Kordova, Tereza; Mareska, Ales; Havlik Mika, Martin (Manufacturing Technology Journal, 2022)
In this paper, the adhesive behaviour of different polyurethane glues was studied and compared. The study was inspired by real conditions in the production of car windows, and it is divided into several parts, which deal with three types of polyurethane adhesives. The first type is a standard one-component polyurethane adhesive, which cures with air humidity. The second type is a one-component polyurethane adhesive with the addition of a curing accelerator. And the third type is a two-component polyurethane adhesive. Adhesive blocks of defined dimensions and plastic parts glued to the glass were used for this experiment to simulate a real product. The influence of temperature and humidity on the curing process was evaluated. The test included measuring the force required to tear the parts from the glass and assessing the type of failure. Based on the achieved results, the adhesives were evaluated regarding their applicability in the real automotive industry and the key properties necessary to maintain the safety and quality of the glued part were determined
Keywords: Adhesion; Polyurethanes; Glass; Manufacturing Technology; Automotive Industry